The Relationship Between Self-Efficacy and Attention to Table Tennis Topspin Technique - Muhammad Agil Nur Riyan; Indra Safari; Dewi Susilawati (Universitas Negeri Semarang, 2026)
Table tennis is a sport that requires a combination of technical skills, physical abilities, and psychological factors, particularly in executing complex techniques such as topspin. In practice, many athletes experience difficulties in performing consistent and accurate topspin strokes, which may be influenced not only by technical mastery but also by psychological aspects such as self-efficacy and attention. This study aims to analyze the relationship between self-efficacy and attention on topspin technique skills in athletes of the UPI Sumedang Table Tennis Student Activity Unit. The study used a quantitative approach with a correlational design. The sample consisted of 15 athletes selected through purposive sampling from a total population of 30 athletes. The research instruments included a self-efficacy questionnaire adapted from Albert Bandura's concept and an attention scale based on Robert L. Solso's cognitive theory, and a topspin skill test. Data analysis used Pearson correlation test and multiple linear regression with the help of SPSS 26 at a significance level of 0.05. The results showed that partially self-efficacy was significantly related to topspin skills (r = 0.538; p = 0.039), and attention was also significantly related (r = 0.758; p = 0.001). However, in the multiple regression analysis, only attention had a significant effect on topspin skills (β = 0.646; p = 0.005), while self-efficacy did not show a significant effect (p = 0.157). Both variables simultaneously contributed 64.2% to topspin skill (R² = 0.642; p = 0.002). These findings indicate that attention is the dominant predictor of topspin skill, while self efficacy plays an indirect role when analyzed together. The implications of this study emphasize the importance of integrating psychological training, particularly attention, into table tennis training programs.